The expression equivalent to -7(y - 2) is -7y + 14
<h3>Which expression is equivalent to -7(y - 2)?</h3>
Given the expression; -7(y - 2)
We expand the expression by multiplying each element inside the parentheses the element out i.e -7
-7(y - 2)
[ -7 × y and -7 × -2 ]
-7y + 14
Therefore, the expression equivalent to -7(y - 2) is -7y + 14.
Learn more about expressions here: brainly.com/question/13947055
#SPJ1
First, you need to find out how many zippers are used to make one bookbag. To do that, you divide the zippers used to make the 3 backpacks.
12 / 3 = 4
So, 4 zippers are used per bookbag. Then, you divide the number of available zippers by four to find out how many bags she can make.
48 / 4 = 12
Roberta can make 12 bookbags.
Answer:
53d
Step-by-step explanation:
Answer:
Step-by-step explanation:
2g + h = 2 --------------(I)
g - h = -5------------(II)
g = -5 + h
Plugin g = -5 + h in equation (I)
2(-5 + h) + h = 2 {Distributive property:a(b+c) = a*b +a*c}
(-5)*2 + h *2 + h= 2
-10 + 2h + h = 2
3h = 2 + 10
3h = 12
h = 12/3
h = 4
Substitute h= 6 in equation (I)
2g + 4 = 2
2g = 2 - 4
2g = -2
g = -2/2
g = -1
Answer:
78 x 160
/100
= 124.8
12 x 325/100
= 39
Step-by-step explanation: